THE RELATIONSHIP BETWEEN FINANCIAL RATIOS AND STOCK PRICES IN THE MANUFACTURING SECTOR COMPANIES IN THE HEALTHCARE AND CONSUMER NON-CYCLICAL SECTORS LISTED ON THE INDONESIAN STOCK EXCHANGE FROM 2019 TO 2023 - Helly Aroza Siregar; Agustian Anggoro; Yenny Wati; Irawati; Zulhelmi (Institut Bisnis dan Teknologi Pelita Indonesia, 2026)
This study aims to determine the effect of several financial ratio which are debt to equity ratio, earnings per share, price earning ratio, dividend payout ratio, and return on equity on the stock prices of manufacturing companies in the Healthcare and Consumer Non-Cyclical sectors listed on the Indonesia Stock Exchange from 2019 to 2023. Secondary data is used in this quantitative study. The sample was selected using a purposive sampling method, resulting in a total of 145 data observations derived from 8 companies over a five-year observation period. The data were analyzed using multiple linear regression analysis with the assistance of SPSS version 31. The results of this study indicate that the debt-to-equity ratio, earnings per share, and price-earnings ratio have a positive and significant effect on stock prices, dividend payout ratio has no effect on stock prices, while return on equity has a negative and significant influence on stock prices. This study implies that investors should adopt a comprehensive approach when evaluating stocks by considering multiple financial indicators simultaneously. For managers, the findings emphasize the importance of sustaining profitability, optimizing capital structure, and maintaining earnings quality to enhance investor confidence and support long-term stock value.